Polygalacturonase and pectin methylesterase activities of CaCl2 treated red-fleshed dragon fruit (Hylocereus polyrhizus) harvested at different maturity - Awang Y.B.; Chuni S.H.; Mohamed M.T.M.; Mohamad R.B.; Hafiza Yahya (Am. J. Agric. Biol. Sci., 2024)
Indexed by SCOPUS